The electronic structure of 2(5H)-thiophenone investigated by vacuum ultraviolet synchrotron radiation and theoretical calculations - Kumar, S. (2023)
This work was also supported by Radiation Biology and Biophysics Doctoral Training Programme (RaBBiT, PD/00193/2012); D.D. thanks the support from the CaPPA Project (Chemical and Physical Properties of the Atmosphere) funded by the French National Research Agency (ANR) through the PIA (Programme d’Investissement d’Avenir) under Contract No. ANR-10-LABX-005; the Région Hauts de France and the Ministère de l’Enseignement Supérieur et de la Recherche (CPER ECRIN) and the European Fund for Regional Economic Development for their financial support. This work was performed using HPC resources from GENCI-TGCC (Grant No. 2022-A0110801859) and the Centre de Ressources Informatiques (CRI) of the Université de Lille. The authors wish to acknowledge the beam time at the ISA synchrotron, Aarhus University, Denmark. GG acknowledges the Spanish Ministerio de Ciencia e Innovación (Project No. PID2019-104727RB-C21) and the EURAMET’s Project 21GRD02 BIOSPHERE. This contribution is also based upon work from the COST Action CA18212-Molecular Dynamics in the GAS phase (MD-GAS), supported by COST (European Cooperation in Science and Technology). Publisher Copyright: © 2023, The Author(s).